Das eigene Leben als ästhetische Fiktion: Autobiographie und Professionsgeschichte - Erben, Dietrich; Zervosen, Tobias (transcript, 2018)
Narratives about »real life« or instruments of personal and professional stylization? Based on prominent examples, professional autobiographies are examined as part of the professional, cultural and social history.